2012
DOI: 10.3126/njms.v1i2.6606
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum bilirubin as a marker of acute gangrenous appendicitis

Abstract: Background: This study has compared the difference in serum bilirubin between patients with gangrenous and non-gangrenous appendicitis. Methods: A prospective analytical study of, 141 patients who underwent appendectomy, from March 2010 to March 2011 in Manipal Teaching Hospital, Pokhara, Nepal was carried out. Clinico-demographic data, Alvarado’s score, total serum bilirubin, total leucocyte count and histopathological report of all the cases were collected in a prestructured proforma. Comparison between gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
3
15
3
Order By: Relevance
“…This in contrast to Ghimire et al, (2012) who found a statistically significant different rise in TSB level in gangrenous appendicitis.…”
Section: Resultscontrasting
confidence: 53%
“…This in contrast to Ghimire et al, (2012) who found a statistically significant different rise in TSB level in gangrenous appendicitis.…”
Section: Resultscontrasting
confidence: 53%
“…Conclusion Bilirubin levels may be high, but remain within normal range, in cases of appendicitis. Therefore, bilirubin levels may be a useful measurement when Increased levels of bacteria enter the portal venous system and invade the hepatic parenchyma which interferes with the excretion of bilirubin resulting in hyperbilirubinaemia [13][14][15] and raised inflammatory markers [16].…”
Section: Introductionmentioning
confidence: 99%
“…22 The study done Hong et al reported that the univariate analysis demonstrated significant differences for TLC (p<0.0001), total bilirubin (p<0.0001) and Alvarado score (p<0.0001). The multivariate analysis demonstrated that…”
Section: Discussionmentioning
confidence: 99%
“…21 Another study Ghimire P et al has stated that 57.7% patients with hyperbilirubinemia had gangrenous or perforated appendix. 22 The study done by Khan S et al there was hyperbilirubinemia in 86.6% of the patient of acute appendicitis bilirubin ranged from 1.2mg/dl-8.4mg/dl. 4 So Authors observed that bilirubin can be important investigation for diagnosing the Appendicular infection.…”
Section: Discussionmentioning
confidence: 99%